'Ogni immagine racconta una storia'. Episodi della ricezione illustrativa dell'Inamoramento de Orlando. (3rd April 2019) - Rizzarelli, Giovanna
ABSTRACT: Unlike the Orlando furioso, the Inamoramento de Orlando, even in its earliest editions, was generally not illustrated by original engravings. Figurative sets produced for other poems, mostly illustrations inspired by the Morgante and the Furioso, were instead deployed to accompany Boiardo's octaves. The essay analyses the figurative reception of the Inamoramento during the sixteenth century, focusing on prominent printing houses that published the poem using engravings that were already available. The essay examines the strategies adopted in reusing the images, paying special attention to how the Furioso 's illustrations were readapted so as to emphasize the relationships between the Inamoramento and its sequel. At the end of the eighteenth century the Inamoramento was eventually illustrated with original engravings. The analysis of the reception of Boiardo's poem through these different phases makes clear how the dynamics of mutual influence connecting the Inamoramento with its sequel also had a visual dimension.